Comparison on the Nutrient Plunder Capacity of Orychophragmus violaceus and Brassica napus L. Based on Electrophysiological Information - Cheng Zhang; Yue Su; Yanyou Wu; Haitao Li; Ying Zhou; Deke Xing (Horticulturae, 2021)
The nutrient metabolism, growth and development of plants are strongly affected by its nutrient plunder, and plants have different adaptive mechanisms to low-nutrient environments. The electrophysiological activities involve almost all life processes of plants. In this study, the active transport flow of nutrient (NAF) and nutrient plunder capacity (NPC) of plants were defined based on leaf intrinsic impedance (IZ), capacitive reactance (IXc), inductive reactance (IXL) and capacitance (IC) to evaluate the nutrient plunder capacity of plants for the first time. The results indicate that Orychophragmus violaceus had higher (p < 0.01) NPC and IC and lower (p < 0.01) IR, IXc, IXL and IZ as compared to Brassica napus L., which supports a superior ion affinity and that it could be better adapted to low-nutrient environments. UAF and NPC of plants exhibited good correlations with crude protein, crude ash and water content, and precisely revealed the plunder capacity and adaptive strategies of plants to nutrients. The present work highlights that O. violaceus had superior NPC and ion affinity compared with B. napus, and provided a novel, rapid, reliable method based on the plant’s electrophysiological information for real-time determination of the nutrient plunder capacity of plants.